Multilayer Perceptron-based Skew-Angle Estimation for Bit-Patterned Magnetic Recording - Kittipon Kankhunthod; Chanon Warisam; Santi Koonkarnkhai; Piya Kovintavewat (2021 36th International Technical Conference on Circuits/Systems, Computers and Communications (ITC-CSCC), 2021)
Bit-patterned magnetic recording (BPMR) is the potential future recording technology that can increase an areal density (AD) of hard disk drives over 1 terabit per square inch (Tbit/in 2 ). Several challenging problems are causing the reduction of a recording system's performance. One of them is a skew angle effect that is depended on the reading and writing position of a reader on a platter. Therefore, this paper proposes the skew-angle (SA) estimation method based on multilayer perceptron using readback signals. The accuracy percentage of the proposed SA estimation method provides above 80% when it was investigated under medium-high signal-to-noise ratio levels.
Keywords: Iterative Learning Control Systems; Neural Networks and Applications; Magnetic properties of thin films